2016
DOI: 10.1523/jneurosci.2517-14.2016
|View full text |Cite
|
Sign up to set email alerts
|

Brain Signal Variability Differentially Affects Cognitive Flexibility and Cognitive Stability

Abstract: Recent research yielded the intriguing conclusion that, in healthy adults, higher levels of variability in neuronal processes are beneficial for cognitive functioning. Beneficial effects of variability in neuronal processing can also be inferred from neurocomputational theories of working memory, albeit this holds only for tasks requiring cognitive flexibility. However, cognitive stability, i.e., the ability to maintain a task goal in the face of irrelevant distractors, should suffer under high levels of brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 41 publications
(1 reference statement)
11
87
0
1
Order By: Relevance
“…These studies primarily measured the blood oxygen level dependent (BOLD) signal using fMRI. For example, it has been demonstrated that the variance of the task-evoked BOLD response was differentially related to aging as well as cognitive performance (Armbruster-Genc et al, 2016;Garrett et al, 2013a). Similarly, spontaneous signal variability in resting state fMRI (rsfMRI) has been associated with age (Grady and Garrett, 2018;Nomi et al, 2017), emotional state (state anxiety; Labrenz et al, 2018), and mental or neural disorders such as stroke (Kielar et al, 2016), Attention Deficit Hyperactivity Disorder (Nomi et al, 2018) or 22q11.2 deletion syndrome (Zöller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These studies primarily measured the blood oxygen level dependent (BOLD) signal using fMRI. For example, it has been demonstrated that the variance of the task-evoked BOLD response was differentially related to aging as well as cognitive performance (Armbruster-Genc et al, 2016;Garrett et al, 2013a). Similarly, spontaneous signal variability in resting state fMRI (rsfMRI) has been associated with age (Grady and Garrett, 2018;Nomi et al, 2017), emotional state (state anxiety; Labrenz et al, 2018), and mental or neural disorders such as stroke (Kielar et al, 2016), Attention Deficit Hyperactivity Disorder (Nomi et al, 2018) or 22q11.2 deletion syndrome (Zöller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the successful pursuit of goals for adaptive purposes also requires a level of cognitive stability or maintenance (4). In fact, a considerable portion of our daily lives comprises learned, automatic, reflexive or habitual behaviors under specific contexts in stable environments, as opposed to the controlled and effortful processes commonly scrutinized in experimental settings (5).…”
mentioning
confidence: 99%
“…In fact, the BSV is primarily increased at resonant frequencies while decreased at nonresonant frequencies, indicating frequency‐specific energy reallocation. The frequency effect challenges the monotonous relationship between BSV and cognitive performance as previously suggested (Garrett et al, ), arguing that the brain can flexibly reallocate energy among different functional subsystems (Armbruster‐Genç, Ueltzhöffer, & Fiebach, ).…”
Section: Discussionmentioning
confidence: 76%